2015
DOI: 10.1111/rmir.12029
|View full text |Cite
|
Sign up to set email alerts
|

Probability Updating and the Market for Directors’ and Officers’ Insurance

Abstract: Over the past decade, much attention has been given to the topics of corporate governance and corporate risk management. One increasingly important insurance product associated with each of these issues is directors' and officers' (D&O) liability insurance. Given the interconnectedness that exists between D&O insurance, corporate risk management, and corporate governance, we exploit industry-specific D&O data to explain how industries most associated with the corporate scandals of the early 2000s adjusted dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…What sets that research apart from previous publications is the quantitative methodology used to assess the D&O insurance market, an unparalleled approach in the Brazilian case. However, the qualitative explanations of Rodrigues (2011) and Faria (2015) about the moments of higher growth of the D&O line in Brazil corroborate the probability updating hypothesis (Fier et al, 2015), since the three years of highest growth observed (2004, 2010, and 2015) were preceded by events that raised the risk perception by economic agents. This research hypothesizes that the performance of D&O insurance in 2015 is related to the outbreak of CWO in 2014.…”
Section: 60%mentioning
confidence: 74%
See 4 more Smart Citations
“…What sets that research apart from previous publications is the quantitative methodology used to assess the D&O insurance market, an unparalleled approach in the Brazilian case. However, the qualitative explanations of Rodrigues (2011) and Faria (2015) about the moments of higher growth of the D&O line in Brazil corroborate the probability updating hypothesis (Fier et al, 2015), since the three years of highest growth observed (2004, 2010, and 2015) were preceded by events that raised the risk perception by economic agents. This research hypothesizes that the performance of D&O insurance in 2015 is related to the outbreak of CWO in 2014.…”
Section: 60%mentioning
confidence: 74%
“…The literature calls this type of increase in demand as probability updating (Browne & Hoyt, 2000;Fier et al, 2015;Froot & O'Connell, 1997). The probability updating is heightened after catastrophic events, due to their severity and to the emphasis given to them by the media.…”
Section: Theoretical Background and Theoretical Background And Empirimentioning
confidence: 99%
See 3 more Smart Citations